Quantum public speaking: The basic for character buildings and life skills - Isnanita Noviya Andriyani; Khoirul Maslahah; Fitriah M. Suud (Journal of Community Service and Empowerment, 2023)
The formation of quality Human Resources is a final step that must be taken to face the challenges in the industrial era 4.0, which do not only rely on academic abilities; the quality of human resources of Indonesia's young generation also needs to be boosted through various soft skills to improve emotional intelligence which will be able to bring the Indonesian nation as a winning nation in the future. One of the most important soft skills is public speaking. This paper describes the importance of public speaking strategies for elementary school students to be able to compete in improving their quality. The research method used is descriptive qualitative with a case study approach. Data collection elaborates more deeply on public speaking strategies through interviews, observations, and documentation. The subjects in this study were 61 students and 15 teachers of Ma'had Permata Islam. The results of this study are strategies that can be done to equip public speaking elementary school students by improving speaking skills, critical thinking skills, improving self-quality, getting used to speaking in front of crowds, and preparing themselves. Public speaking for elementary school students is the practice of using learning by doing, where students are trained to be confident and dare to come forward and express opinions. Equipping elementary school students with knowledge of public speaking skills to be fully confident when presenting themselves to the public as a basis for character building and life skills.